Translating Procedures of Islamic Terms in Islam between War and Peace - Ahmad Murodi (Journal of Language and Literature, 2020)
Translation has the purpose to make the audience understand the message and information delivered by the author. The result of translation is considered successful if the translated text can provide similar meaning to the original text. The translation needs procedures because the procedure of translation is the step of activity to complete translation. Translation Procedures (TPs) are of utmost importance all throughout the work of translation. Religious and cultural principles influence different linguistic items in both languages. This research discusses translation procedures that were applied by the translator in the book Islam between War and Peace created by Yakub and comparing the data using Arabic and English dictionary. The objective of this research is aimed to know translation procedures were used by the translator especially in Islamic terms. Qualitative method to produce descriptive data in the form of describing the translation procedures proposed by Newmark was used. The data was conducted by reading the source language (henceforth SL) and the target language (henceforth TL) text, classifying the words based on the types of translation procedures proposed by Newmark, and analyzing the terms or words by Arabic and English dictionary. After analyzing the data, eight types of translation procedures proposed by Newmark are found in the translation of Islam between War and Peace book that contains twenty-six data. They are: Literal ,Transference, Naturalization, Reduction, Addition, Notes, Paraphrase, and Transposition. The translator tries to keep originality and make readers easier to understand what is written in the book.